PENERAPAN STUDENT TEAMS ACHIEVEMENT DIVISION DISERTAI MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PEMASARAN - Nurdina, Husna; Joyoatmojo, Soetarno; Wahyuni, Sri (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2016)
This research is aimed to improve students’ learning outcomes in Introduction to Business Economy  in class X Marketing 1 in SMK Negeri 1 Karanganyar through the implementation of cooperative learning model Student Teams Achievement Division (STAD) with picture media. This research is a Classroom Action Research (CAR). The study was conducted in two cycles, with each cycle consisting of planning, action, observation and reflection. The subjects were 37 students of class X Marketing 1 SMK Negeri 1 Karanganyar. The source of data derived from students, teachers, and documents. The data collection techniques are observation, testing, documentation and interviews. The techniques for the validity of the data used triangulation of data sources. The data analysis used descriptive analysis technique, the technique of qualitative analysis and comparative description.The results showed that through the implementation of cooperative learning model Student Teams Achievement Division (STAD) with picture media can improve learning outcomes in Introduction to Business Economics (PEB) in class X Marketing 1 SMK Negeri 1 Karanganyar in the Academic Year 2015/2016. It was proved by an increasing in the first cycle and the second cycle. Before applied cooperative learning model Student Teams Achievement Division (STAD) with picture media of the class average value was 73.27 with a percentage of 37.84% completeness. In the first cycle class average value increased to 80.97 with the percentage of 81.08% completeness and the second cycle class average value increased to 97.35 with the percentage of completeness 100%. The conclusions of this research is the application of cooperative learning model Student Teams Achievement Division (STAD) with picture media can improve learning outcomes in Introduction to Business Economics (PEB) in class X Marketing 1 SMK Negeri 1 Karanganyar in the year of 2015/2016.